Updating of Makiling Biodiversity Information System (MakiBIS) and Analysis of Biodiversity Data - DAMASA MAGCALE-MACANDOG; Fermin Roberto Lapitan; Jeoffrey Laruya; Jandrel Ian Valerio; JANZEN CHRISTIAN D. AGUILA; CLOUIE ANN L. MESINA; TWINKLE MARIE F. SANTOS; ANDREA NICOLE T. CUEVAS; KIMBERLY D. BAYLON; IANA MARIENE SILAPAN; RICAJAY DIMALIBOT; JENNIFER D. EDRIAL; NETHANEL JIREH A. LARIDA; FATIMA A. NATUEL; MA. GRECHELLE LYN D. PEREZ; SARENA GRACE L. QUINONES (Society for Indonesian Biodiversity, 2021)
Abstract. Magcale-Macandog DB, Lapitan FRG, Laruya JM, Valerio JIF, Aguila JCD, Mesina CAL, Santos TMF, Cuevas ANT, Baylon KD, Silapan IM, Dimalobot R, Edrial JD, Larida NJA, Natuel FA, Perez MAGLD, Quinones SGL. 2021. Updating of Makiling Biodiversity Information System (MakiBIS) and Analysis of Biodiversity Data. Biodiversitas 22: 211-226. Mt. Makiling is a Philippine biodiversity hotspot listed as one of the 170 conservation priority areas established by the Philippine government. With the vast amount of ecological and biological information about the flora and fauna of Mt. Makiling, the Makiling Biodiversity Information System (MakiBIS) was developed to serve as a repository for these data. MakiBIS may serve as a prototype in the development of a national BIS that will be useful in addressing the need to set a national baseline, measurable targets, and indicators to facilitate the assessment of biodiversity status and as a basis for decision-making.The MakiBIS project started in 2011 and was last updated in 2014. In 2019, a new version of the information system was updated to take advantage of current web technologies in software development. The new MakiBIS’ (MakiBIS 2.0) frontend was written using ReactJS, while its backend functions were coded using NodeJS, and the database tables were compressed and optimized for faster queries. MakiBIS 2.0 was published online and can be accessed at www.makibis.com.The MakiBIS 2.0 database was populated with biodiversity information from published botanical and faunal survey studies conducted in Mt. Makiling. Biodiversity information includes taxonomic classification, botanical description, habitat, mode of reproduction, economic use, endemism, and conservation status. The MakiBIS database was analyzed for patterns, trends, distribution, and potential threats that will be useful towards the conservation and management of these biodiversity resources.